If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 25 + -12x = 13 Solving 25 + -12x = 13 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-25' to each side of the equation. 25 + -25 + -12x = 13 + -25 Combine like terms: 25 + -25 = 0 0 + -12x = 13 + -25 -12x = 13 + -25 Combine like terms: 13 + -25 = -12 -12x = -12 Divide each side by '-12'. x = 1 Simplifying x = 1
| b-11=-8 | | 3x^2-9x-27=0 | | (8x-3)(x+2)=4 | | 8x+2-6x=1+x-8 | | -35/12=20/3x | | 10y-11=-2 | | 8-8x=20x+19 | | F-12=1 | | 3x-4+6=2x+8 | | -1/11x=7 | | 6(z+9)-(9+4z)=z | | 6y-5=7y+9 | | 2x+4x-3=9 | | f(x)=x^3-x | | 1/2(6x-8)+3(x+2)=4(2x-1) | | 12-4u+u=22+2u | | 5x-3x+x=3 | | x*20/3=4/9 | | -8(z-3)=5-7z | | 12x100/2 | | -22k-39k= | | -8(2-3)=5-7z | | f(14)= | | 158-6x=5x+15 | | 4x^2-19x+17=0 | | (x/3)=4 | | x+2x-15=21 | | 12.4x+7.7=82.1 | | 6-9x=60-23x | | x^2+x-(-2x)=x^2+12 | | -1/8*9 | | 25*7*6+8+8-79= |